The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21203/rs.3.rs-34757/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors influencing early initiation of breastfeeding among mothers in Rajshahi district, Bangladesh

Abstract: Background Early initiation of breastfeeding (EIBF) is referred as providing the breast milk to the newborn within one hour of birth which ensures that the infant receives the colostrum. The aim of this study was to identify the risk factors associated with early initiation of breastfeeding among mothers in Rajshahi district, Bangladesh. Methods The data was collected from mothers living in Rajshahi district who had at least one child aged 6–24 months from January to March, 2019. The EIBF was measured by a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…27 Another study in the Rajshahi area of Bangladesh found that the prevalence of early breastfeeding beginning was 88.4%, which is remarkably similar to our findings due to the similar sociodemographic profile. 28 Alternatively, a lower rate of moms initiating nursing early and offering breast milk to their child immediately after delivery was observed in various areas of the country, with only 46.9% doing so in Jessore district. 26 The prevalence of EBF (early breast feeding) in this study was below medium range, which is in line with findings of other studies in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another study in the Rajshahi area of Bangladesh found that the prevalence of early breastfeeding beginning was 88.4%, which is remarkably similar to our findings due to the similar sociodemographic profile. 28 Alternatively, a lower rate of moms initiating nursing early and offering breast milk to their child immediately after delivery was observed in various areas of the country, with only 46.9% doing so in Jessore district. 26 The prevalence of EBF (early breast feeding) in this study was below medium range, which is in line with findings of other studies in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption process was fast at the beginning then it became slow and finally it reached maximum occupancy of the active sites of the modified CLN by the Rh B molecules and did not show the further effects of time. This is due to a greater number of vacant sites available in the beginning that are gradually occupied by the dye molecules [30]. Similarly, the increased percentage of adsorption of the solution with shaking was due to the dispersion of analyte molecules uniformly throughout the solution making it easy for the analyte molecules to adhere to the adsorbent.…”
Section: Optimization Of Contact Time For Adsorption Of the Rh B By T...mentioning
confidence: 99%
“…For this reason, mild syntheses are advisable or the introduction of natural-based components could also enhance the environmental-friendliness. Common materials from natural-based origin found in the literature include chitosan/poly(vinyl alcohol) electrospun nanofibers, 147 cellulose, 148,149 alginate, 150 starch, 151 and even biowaste. 152 Feng and co-workers 153 packed natural cotton fiber into a polyetheretherketone (PEEK) tube (i.d.…”
Section: Analytical Chemistry Pubsacsorg/acmentioning
confidence: 99%